Interaction of Nanoatrazine and Target Organism: Evaluation of Fate and Photosystem II Inhibition in Hydroponically Grown Mustard (Brassica juncea) Plants - Preisler, Ana Cristina; Carvalho, Lucas Bragancą [UNESP]; Saraiva-Santos, Telma; Verri, Waldiceu Aparecido; Mayer, Juliana Lischka Sampaio; Fraceto, Leonardo Fernandes [UNESP]; Dalazen, Giliardi; Oliveira, Halley Caixeta (American Chemical Society (ACS), 2022)
Poly(epsilon-caprolactone) nanoparticles are an efficient carrier system for atrazine. However, there is a gap regarding the effects of nanoencapsulation on herbicide-plant interactions. Here, we evaluate the fate and photosystem II inhibition of nano and commercial atrazine in hydroponically grown mustard (Brassica juncea) plants whose roots were exposed to the formulations. In addition, to quantify the endogenous levels of atrazine in plant organs, we measured the inhibition of photosystem II activity by both formulations. Moreover, the fluorescently labeled nanoatrazine was tracked in plant tissues using confocal microscopy. The nanoencapsulation induced greater inhibition of photosystem II activity as well as higher accumulation of atrazine in roots and leaves. The nanoparticles were quickly absorbed by the roots, being detected in the vascular tissues and the leaves. Overall, these results provide insights into the mechanisms involved in the enhanced preemergent herbicidal activity of nanoatrazine against target plants.
Keywords: fluorescence; mechanism of action; nanopesticides; polymeric nanoparticles